Differences in failure patterns according to the EGFR mutation status after proton beam therapy for early stage non-small cell lung cancer. (August 2020) - Nakamura, Masaki; Kageyama, Shun-ichiro; Udagawa, Hibiki; Zenke, Yoshitaka; Yoh, Kiyotaka; Niho, Seiji; Hojo, Hidehiro; Motegi, Atsushi; Kirita, Keisuke; Matsumoto, Singo; Goto, Koichi; Akimoto, Tetsuo
Abstract: We analyzed 135 patients (including 27 EGFR -mutant and 29 EGFR -wild) with T1-3N0M0 non-squamous NSCLC treated by PBT. Considering the 3-year cumulative incidence, the EGFR -mutant group showed a significantly lower infield failure rate (9% vs 27%, p  = 0.02) and higher out-of-field failure rate (67% vs 40%, p  = 0.02) than the EGFR -wild group.